La construction du paysage viticole - Solène Delebecque (Projets de Paysage)
This article interrogates the link between the wine-growers’ practices and the construction of the vineyard landscape, with particular interest in the wine-growers’ perception and their involvement, both material and intellectual, in the process of landscape building. The simple assessment of landscape’s organization is not sufficient to explain its building, so we tried to understand the logic of landscapes production through the reasons that guide the viticulturalists’ choices. First, the analyse the individual practices, lets understand what are the criterions influencing the choices at the scale of parcels. Then, the focus on the collective dimension (the social group of winemakers) precises the dynamics that guide the construction of the vineyard landscape, and thus shows that there is an awareness of the landscape as a collaborative work.